Generalized Formalization Related Signs of Functioning Ergo Technical Information Electronic Systems on the Basis of Their Structural and Logical Models - A. N. Potapov (Известия высших учебных заведений России: Радиоэлектроника)
Performed a generalized formalization related signs of functioning ergo technical information radio electronic systems (RES), which allows to solve the problem of unified description of the functioning of the RES, with invariance to their substantive appointment. The possibility of implementation of the RES functions selection, allocation and reallocation of resources depend on its inherent mechanisms of control. On the basis of a unified approach to the representation of the RECs, as well as given their handling, refined structural and logical description of ergo technical RES.